Awareness of Clinical Trials Participation among Healthy Volunteers - Yusof, Y.; Esraa; S, Matthews.; Halim, R.; Nor, M. Z.; Khalid, A.M.; Desa, M.R. (International Journal of Psychosocial Rehabilitation, 2020)
Clinical trials (CTs) are important part of improving quality of health care. However, recruitment is a major challenge for many trials globally. Likewise, in Malaysia one study that focused on the barriers to CTs participation found that patient participation in cancer CTs is extremely low. Various factors were identified including lack of transportation, lack of interest, job commitment, and medical problems. Nevertheless, until today no study has been conducted to examine the awareness of participation among healthy volunteers. Hence, this study aimed to investigate the reasons why individuals’ wish and wish not to participate in CTs. A case study survey design was used for data collection and analysis of randomly selected staff and students of Universiti Utara Malaysia. A questionnaire was developed to derive effective outcomes based on literature review. Of 2066 participants invited to take part in the survey, 927 (45%) filled the questionnaire. Most of the participants had never participated in a CT (97.2%). The majority of the population was female, aged 18 to 24 years, well educated, and aware of CT from internet. Only 358 (2-6.9%) participants would definitely participate in CT compared to 482 participants who chose possibly and 87 chose never to participate. Low understanding of CT was the main reason that made them to be hesitant whether or not to participate in CT. The majority (36.6%) were motivated to participate to improve personal health aspects. However, fear of risks or complication involved in CT was the main reason (20.2%) that reduced their motivation to participate. The results of this study revealed that younger population have awareness of CT but chose not to participate. Knowledge and a sound understanding of CT is required to motivate their participation in future.